KAT2A succinyltransferase activity-mediated 14-3-3ζ upregulation promotes β-catenin stabilization-dependent glycolysis and proliferation of pancreatic carcinoma cells. (28th January 2020) - Tong, Yingying; Guo, Dong; Yan, Dong; Ma, Chunmin; Shao, Fei; Wang, Yugang; Luo, Shudi; Lin, Liming; Tao, Jingjing; Jiang, Yuhui; Lu, Zhimin; Xing, Dongming
Abstract: Frequently occurring histone lysine succinylation is a newly identified histone modification that can be regulated by KAT2A histone succinyltransferase, which is also a histone acetyltransferase. KAT2A histone succinyltransferase activity is important for tumorigenesis; however, the mechanism underlying this tumor-promoting effect remains elusive. Here we demonstrate that KAT2A is highly expressed in human pancreatic ductal adenocarcinoma (PDAC) specimens and positively correlated with advanced stages of PDAC and short patients' survival. In addition, KAT2A expression in PDAC specimens is correlated with 14-3-3ζ expression, and KAT2A regulates H3K79 succinylation in the promoter region of YWHAZ (encoding for 14-3-3ζ) to promote YWHAZ mRNA and 14-3-3ζ expression, thereby preventing β-catenin degradation. Expression of succinyltransferase activity-defective KAT2A Y645A reduces H3K79 succinylation and 14-3-3ζ expression, leading to decreased β-catenin stability and subsequently decreased expression of cyclin D1, c-Myc, GLUT1, and LDHA. KAT2A-mediated 14-3-3ζ and β-catenin expression promotes glycolysis, cell proliferation, and migration and invasion of PDAC cells with epithelial-to-mesenchymal transition. These findings reveal a novel and instrumental role of KAT2A-mediated histone succinylation in regulation of gene expression and β-catenin stability to promote tumor cell proliferation and invasion. Highlights: KAT2A is upregulated in human pancreatic ductal adenocarcinoma and correlated with poor prognosis. KAT2A regulates H3K79 succinylation in the promoter region of YWHAZ to promote its mRNA expression. KAT2A-upregulated 14-3-3ζ expression stabilizes β-catenin. KAT2A-upregulated β-catenin expression promotes glycolysis, proliferation, and invasion of PDAC cells.